Geographical Information System Mapping the Billboards In Samarinda - Lidiya Suryaningsih; Wahyuni Eka Sari; Dawamul Arifin (TEPIAN, 2020)
Advances in information technology on geography are increasingly needed by many people, for example information on distances between regions, locations, facilities and many other information. The information is needed by users for various purposes such as research, development, regional design and natural resource management. Because of this geographical presence can help the presentation of a more interactive information, where users can access complete geographical information using only a computer, web-browser and internet network. So to get that information all in need of a Geographical Information System (GIS). The purpose of this research is to create a web that contains information on the location of billboards in the city of Samarinda. While this research is expected to make it easier for users to obtain information on the location of billboards in Samarinda.